GPS Locator With Google Map Interface - Noorfarizza, Abd Maulud (UTeM, 2011)
This project aim is to develop a Global Positioning System (GPS) Locator interface using Google Map. The interface enable user to explore and able to get the information on GPS with the assist from Google Map. The interface will be developed using Visual Basic program (VB), that in combination with Web Google Map application. This interface will be portraying location use Google Map that require by GPS Locator by coordinate input from GSM communication system (Global System for Mobile Communication). GSM modem will be used to accept data from any GPS. This GSM modem will be connected to computer and coordinate data will be processed using Visual Basic and display map to that location according to coordinate .A part from GSM, PIC (Peripheral Interface Circuit) Microcontroller Circuit also been used to send coordinate data, this enable that delivery procedure comparison been made between use GSM and also PIC. However the purpose still similar which is, to display that data location using interface of Google Map.